Mutations in STK11 gene in Czech Peutz-Jeghers patients - Vasovcák, Peter; Puchmajerová, Alena; Roubalík, Jan; Krepelová, Anna (BMC medical genetics, 2009)
BACKGROUND: Peutz-Jeghers syndrome (PJS) is an autosomal dominant hereditary disease characterized by mucocutaneous pigmentation and gastrointestinal hamartomatous polyposis. The germline mutations in the serine/threonine kinase 11 (STK11) gene have been shown to be associated with the disease. Individuals with PJS are at increased risk for development of various neoplasms. The aim of the present study was to characterize the genotype and phenotype of Czech patients with PJS. METHODS: We examined genomic DNA of 8 individuals from five Czech families by sequencing analysis of STK11 gene, covering its promotor region, the entire coding region and the splice-site boundaries, and by multiplex ligation-dependent probe amplification (MLPA) assay designed for the identification of large exonic deletions or duplications of STK11 gene. RESULTS: We found pathogenic mutations in STK11 gene in two families fulfilling the diagnostic criteria of PJS and in one of three sporadic cases not complying with the criteria. The patient with the frameshift mutation in STK11 gene developed aggressive gastric cancer. No other studied proband has developed a carcinoma so far. CONCLUSION: Our results showed that a germline mutation of STK11 gene can be found not only in probands fulfilling the PJS diagnostic criteria, but also in some sporadic cases not complying with the criteria. Moreover, we observed a new case of aggressive gastric cancer in a young patient with a frameshift mutation of STK11 gene.
Keywords: zárodečné mutace; dospělí; Germ-Line Mutation; Female; dítě; předškolní dítě; Adult; ženské pohlaví; mutační analýza DNA; Peutz-Jeghers Syndrome; lidé; posunová mutace; AMP-Activated Protein Kinase Kinases; DNA Mutational Analysis; Protein Serine-Threonine Kinases; Frameshift Mutation; Middle Aged; Male; Czech Republic; Child, Preschool; Česká republika; Peutzův-Jeghersův syndrom; lidé středního věku; kinasy AMP aktivovaných proteinkinas; Child; mužské pohlaví; protein-serin-threoninkinasy; Humans